The Severity of Corruption Factors in Project Life Cycle from Construction Experts’ Perspectives - Mohd Saim, Nur Amylia Izrin; Abdul Rahman, Ismail; Ismail, Mohd Firdaus (International Journal of Sustainable Construction Engineering and Technology, 2020)
A study was conducted to identify whether corruption factors extracted from the literature review are relevant to the local construction industry. This study involves 13 construction experts that have been selected based on their experiences and prominent position in their respective organizations. All of the experts have a minimum of 10 years of working experiences, and their jobs are ranging from engineer to project manager. The experts were given a questionnaire and required to score the degree of severity to each of the 31 corruption factors in 4 stages of Construction Project Life Cycle (CPLC). Data collected from this study were analyzed descriptively using Average Index Score approach. The result of the study indicated that all the factors were getting scores ranging from 2.54 to 3.77, which indicates that the factors range from moderately relevant to extremely relevant from the viewpoints of the experts. Three highest scored factors are "High of competitions amongst contractor"; "Political influence in the design and tendering stage"; "Abuse of power from the client". Findings from this study can be further explored and applied to respective construction parties in decision making.